Effect of Boron on Yield Attributes, Seed Yield and Oil Content of Mustard (Brassica juncea L.) on an Inceptisol - and Omkar Kumar, S.N. Yadav, S.K. Singh (Journal of the Indian Society of Soil Science, 2016)
A field experiment was conducted at Agriculture Research Farm, Banaras Hindu University, Varanasi, during two consecutive rabi season of 2012-2013 and 2013-2014 to study the effect of boron (B) on growth, yield and quality of mustard (Brassica juncea L.). The experiment comprised of 11 B levels i.e., 0, 0.5, 1.0, 1.25, 1.5, 1.75, 2.0, 2.25, 2.50, 2.75 and 3.0 kg B ha-1. The results revealed that the highest number of siliqua plant-1 (242 and 245), length of siliqua (5.3 and 5.4 cm), number of seeds siliqua-1 (16.3 and 16.2), seed yield (1.89 and 2.02 t ha-1), oil content (35.5 and 36%) were recorded where 1.5 kg B ha-1 was applied, while maximum protein content (22.2 and 21.9%) was noticed with application of 1.75 kg B ha-1 during 2012-13 and 2013-14, respectively. Application of 1.5 kg B ha-1 gave average increase in seed yield of 36% and oil yield of 52%. It also increased the uptake of B by seed and stover significantly over control.